A high flame retardant and low heat release polyolefin sheath material and preparation method thereof

By developing a high flame retardant and low heat release polyolefin sheath material, combined with ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer and other materials, and adding aluminum hydroxide, magnesium hydroxide, carbon-forming agent and other components, the problems of insufficient flame retardant performance and poor processing performance of existing sheath materials are solved, and the high flame retardant, low heat release and easy carbon-forming properties of wire and cable sheath materials used in high-rise public buildings and crowded places are achieved.

CN116462903BActive Publication Date: 2025-03-28ZHEJIANG WANMA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310422464.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-03-28
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

When the existing halogen-free low-smoke cable sheath material is used in high-rise public buildings and crowded places, the flame retardant performance is insufficient, which can easily lead to the thermal release rate and combustion drips not meeting the standards, and the processing performance is poor, making it difficult to meet higher flame retardant and durability requirements.

Method used

A high flame retardant and low heat release polyolefin sheath material is developed. By reasonably preparing ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer, metallocene linear low-density polyethylene and other materials, and adding aluminum hydroxide, magnesium hydroxide, carbon-forming agent and other components, it is processed through a twin-screw extruder to form a sheath material with excellent flame retardant shell properties and easy carbon formation characteristics.

Benefits of technology

The high flame retardant, low heat release and easy carbonization performance of wire and cable sheath materials used in high-rise public buildings and crowded places is achieved, avoiding the risk of burning drips and improving the safety and service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high flame retardant and low heat release polyolefin sheath material and a preparation method thereof, including ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer, metallocene linear low-density polyethylene, compatibilizer, silicone masterbatch, carbon black masterbatch, aluminum hydroxide, magnesium hydroxide, antioxidant, silane coupling agent and carbon forming agent, with quaternary ammonium salt organic intercalation nanosheet structure montmorillonite as the main carbon forming agent, mica powder, wollastonite, white carbon black as porcelain skeleton, and adding a small amount of ceramic zinc borate and other low melting point flux to help sheath porcelain. The high flame retardant and low heat release polyolefin sheath material developed by the present invention, the plastic particles extruded by twin screws, the performance is completely better than the customer's technical requirements, and the finished wire and cable processed by extrusion has the characteristics of no dripping, easy carbonization, no combustion support, flame retardant crusting, etc. in the combustion test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, relates to sheath materials, and in particular to a highly flame-retardant and low heat-release polyolefin sheath material and a preparation method thereof. Background Art

[0002] Halogen-free and low-smoke cable materials for wires and cables are generally mixed with resin materials, fillers, plasticizers, antioxidants, flame retardants and antioxidants. The raw materials in the formula are all some commonly used materials, which cannot meet the transmission and wiring needs of cables in domestic high-rise public buildings, special sports buildings, special exhibition buildings, underground public buildings (comprehensive shopping malls, subway stations), catering and other crowded public places, especially the Guangdong Provincial Local Standard DBJ / T 15-226-2021 "Technical Code for Fire Protection of Wires and Cables in Civil Buildings", which stipulates the flame-retardant B1 grade products and bundled Class A, Class B and Class C in the same channel.

[0003] The technical performance of the halogen-free polyolefin wire and cable sheath materials currently used is not high or the cost is high, and they cannot meet the wire and cable manufacturers' requirements for higher and better flame retardant properties of sheath materials, especially the d0 level regulations for burning drips during the 20 minute burning process.

[0004] Although the performance of the halogen-free sheath materials currently used meets the requirements of GB / T32129-2015 "Halogen-free and low-smoke flame-retardant cable materials for wires and cables" and has excellent flame-retardant encrusting performance, according to GB31247, during the combustion process, the sheath after encrustation is very likely to fall off or drip in small pieces during the test, resulting in the heat release rate and combustion dripping not meeting the standards.

[0005] At present, the wire and cable manufacturers usually produce flame retardant B1 grade or flame retardant B1 grade A double flame retardant halogen-free cables, which use diamond mud materials, fireproof mud materials, ceramic polyolefin materials and polyolefin oxygen insulation sheath materials. This kind of material has two major disadvantages: first, the bending performance of diamond mud materials, fireproof mud materials and polyolefin oxygen insulation sheath materials is poor, and they are very easy to absorb moisture and break; the crusting performance of ceramic polyolefin materials is general, but the material has almost lost its plasticity and has poor moisture resistance. The design of similar materials, when used in wire and cable products, will bury hidden dangers to the quality and service life of the products; second, the extrusion processing performance of diamond mud materials, fireproof mud materials, polyolefin oxygen insulation sheath materials and ceramic polyolefin materials is poor, the production efficiency is low, they are easy to disconnect and break when bent; diamond mud materials, fireproof mud materials and polyolefin oxygen insulation sheath materials are mainly used in the inner lining layer of cables, and ceramic polyolefin materials are mainly used in the outer sheath of cables. Summary of the invention

[0006] In order to solve the above problems, the present invention develops a highly flame-retardant and low-heat-release polyolefin sheath material and a preparation method thereof according to the performance requirements of halogen-free and low-smoke wire and cable products and the characteristics of sheath production and processing technology, and meets the requirements of additional information dripping d0 level. The product of the present invention can be operated for a long time in special and first-class places, and is mainly used in domestic high-rise public buildings, special sports buildings, special exhibition buildings, underground public buildings (comprehensive shopping malls, subway stations), restaurants and other crowded public places. The material has the characteristics of no dripping, good flame retardant crusting, easy carbonization, non-combustibility, and non-toxicity.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention first provides a highly flame-retardant and low-heat-release polyolefin sheath material, which comprises, by weight: 17-21 parts of ethylene-vinyl acetate copolymer, 4-6 parts of polyolefin thermoplastic elastomer, 44.1-57 parts of metallocene linear low-density polyethylene, 3.0-5.5 parts of a compatibilizer, 1.0-1.7 parts of a silicone masterbatch, 1.5-2.3 parts of a carbon black masterbatch, 47-58 parts of aluminum hydroxide, 19-29 parts of magnesium hydroxide, 0.5-1.2 parts of an antioxidant, 0.5-1.3 parts of a silane coupling agent and 2.7-4.3 parts of a carbon-forming agent.

[0009] In the present invention, at the initial stage of fire combustion, aluminum hydroxide and magnesium hydroxide decompose to produce water vapor, which can dilute the combustibles produced by the decomposition of organic matter and take away heat, thereby playing a role in flame retardancy and slowing down the fire; nano-sheet montmorillonite is used as a carbon-forming agent, which can fix the components in the composite material at the initial stage of combustion to prevent the high-temperature dripping phenomenon of the composite material during the combustion process; after the decomposition of magnesium hydroxide and aluminum hydroxide is completed, the low-melting-point flux begins to melt at above 500°C, and eutectics with mica, wollastonite, white carbon black, and aluminum oxide and magnesium oxide produced by the decomposition of aluminum hydroxide and magnesium hydroxide, and finally eutectics with mica, wollastonite, etc. at about 800°C, and forms a porous ceramic structure together with other decomposition products and fillers, and the structure covers the surface of the cable to play a role in fire insulation and heat insulation, thereby protecting the internal core of the cable.

[0010] The invention is innovatively developed on the basis of thermoplastic 90°C halogen-free low-smoke flame-retardant polyolefin sheath material according to bundle flame-retardant test and flame-retardant B1 test data. The invention has excellent process performance and is easy to produce. The processed high flame-retardant, low heat release, easy carbonization, low smoke and non-toxic polyolefin sheath material has an oxygen index of medium to high, with actual measured values ​​ranging from 33% to 37%, excellent flame-retardant crusting performance, and better light transmittance than other similar products, with actual measured values ​​greater than 70%. During the 20-minute burning process, the sheath combustion drips / particles level reaches the highest level d0 level (no combustion drips / particles within 1200 seconds). According to the standard GB / T19666, the ability of the product to suppress the vertical spread of flames is simulated when a fire occurs. The measured test values ​​of the bundled flame retardant A, B, and C are respectively lower than 0.83 meters, 0.49 meters, and 0.35 meters; according to the standard GB31247, by simulating the combustion scene when a fire occurs, the total heat release, combustion growth rate, heat release rate, smoke production rate, total smoke production, and burning dripping data in the process are used to reflect the danger of fire spreading along the cable; and through the detection of light transmittance and smoke toxicity, the importance of visibility and smoke toxicity to personnel escape and safety during the fire process is explained. Through two standards, the flame retardant performance is evaluated and considered from all aspects and angles. It escorts the power transmission of various high-rise public buildings, special sports buildings, special exhibition buildings, underground public buildings (comprehensive shopping malls, subway stations), restaurants and other public places with dense crowds.

[0011] The physical and mechanical properties of the sheath of the halogen-free products extruded from this material meet the requirements of national standards GB / T12706, GB / T11017, GB / T18890 and GB / T22078. During the flame retardant B1 test according to GB31248, the measured values ​​of the peak heat release rate HRR, the total heat release THR within 1200s of fire, and the peak smoke production rate SPR are all better than those specified in the standard. At the same time, there are no burning drips / particles within 1200s of fire. This is far superior to most halogen-free and low-smoke flame-retardant polyolefin sheath materials on the market, and can effectively avoid the risk of burning drips falling off in whole pieces during the combustion process.

[0012] The present invention is developed according to the design acceptance standards for wire and cable products and the actual needs of the present invention based on the performance of the thermoplastic 90°C halogen-free low-smoke flame-retardant polyolefin sheath material. The product can be operated for a long time in special and first-class places, and is mainly used in domestic high-rise public buildings, special sports buildings, special exhibition buildings, underground public buildings (comprehensive shopping malls, subway stations), restaurants and other crowded public places. The material has the characteristics of no dripping, good flame retardant crusting, easy carbonization, no combustion support, and non-toxicity.

[0013] As a preferred embodiment of the present invention, the carbon-forming agent is prepared from the following raw materials in parts by weight: 0.15-0.34 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 0.7-1.05 parts of mica powder, 1.37-1.65 parts of wollastonite, 0.08-0.12 parts of white carbon black and 0.4-1.14 parts of ceramic zinc iodate.

[0014] In the present invention, the carbonization design scheme is: using quaternary ammonium salt organic intercalated nanosheet structure montmorillonite as the main carbonizing agent, mica powder, wollastonite, and white carbon black as the porcelain skeleton, and adding a small amount of ceramic zinc borate and other low melting point flux to help the sheath porcelainization. The characteristics of the material carbonization system design in the present invention are as follows: according to the flame retardant effect of aluminum hydroxide and magnesium hydroxide in the material formula; adding organic intercalated montmorillonite can fully open the nano-layered structure of montmorillonite, so that the compatibility of montmorillonite with the organic matrix is ​​improved, and its nano-layered structure can increase the melt strength of the composite material during the combustion process to prevent dripping; mica wollastonite and white carbon black porcelain skeleton can form a strong ceramic structure at high temperature, so that the carbon layer of the composite material is strong and not easy to break when it is burned; and the flux is used to reduce the porcelain temperature. Usually, the porcelain temperature of mica powder, wollastonite, etc. is above 1200°C, while the flux begins to melt above 500°C, and can be eutectic with the porcelain skeleton material mica powder, etc. at 600-800°C, and a eutectic reaction occurs to reduce the porcelain temperature.

[0015] As a preferred embodiment of the present invention, the aluminum hydroxide is ultrafine aluminum hydroxide with a particle size of 1 μm-3 μm.

[0016] As a preferred embodiment of the present invention, the magnesium hydroxide is ultrafine magnesium hydroxide with a particle size of 1 μm-3 μm.

[0017] As a preferred embodiment of the present invention, the antioxidant includes 0.3-0.5 parts of antioxidant 300# or antioxidant 1024 and 0.2-0.7 parts of antioxidant DLTP.

[0018] As a preferred embodiment of the present invention, the specific gravity of the quaternary ammonium salt organic intercalated nanosheet structure montmorillonite is 1.9 g / cm 3 .

[0019] As a preferred solution of the present invention, the particle size of the ceramic zinc borate is 2 μm-4.5 μm, and the attached water content is no more than 1%.

[0020] The present invention also provides a method for preparing the above-mentioned highly flame-retardant and low heat-release polyolefin sheath material, the preparation method comprising the following steps:

[0021] 1) Weighing ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer, metallocene linear low-density polyethylene, compatibilizer, silicone masterbatch, carbon black masterbatch, aluminum hydroxide, magnesium hydroxide, antioxidant and silane coupling agent according to the formula, mixing and stirring evenly, stirring for a period of time, heating and continuing to mix, to obtain a mixed material A;

[0022] 2) Weigh the raw materials of the carbonizing agent, mix and stir them evenly, stir for a period of time, increase the temperature and continue mixing to obtain a mixed material B;

[0023] 3) Mixing the mixed material A obtained in step 1) and the mixed material B obtained in step 2) and stirring them, and then kneading them to obtain a mixed material C;

[0024] 4) The mixed material C obtained in step 3) is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat release polyolefin sheath material.

[0025] As a preferred embodiment of the present invention, in step 1), the stirring parameters are: stirring frequency is 8000-10000 rpm, stirring for 5-9 minutes, heating to 95-110° C., and mixing for 11-17 minutes;

[0026] In step 2), the stirring parameters are: stirring frequency is 5000-7000 rpm, stirring for 3-7 minutes, heating to 115-130° C., and mixing for 5-9 minutes;

[0027] In step 3), the stirring parameters are: stirring frequency is 5000-7000 rpm, and stirring is for 3-7 minutes.

[0028] As a preferred embodiment of the present invention, in step 4), the granulation temperature is 130-150°C, and the highly flame-retardant and low heat-releasing polyolefin sheath material is a cylindrical granular material with a particle size of 3-4 mm in diameter and 3 mm in height, or other shapes of comparable size.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1) The highly flame-retardant and low heat release polyolefin sheath material of the present invention is a flame-retardant material that can meet the requirements of the bundled flame-retardant Class A, Class B and Class C specified in the standard GB / T19666, and can also meet the requirements of the flame-retardant Class B1 and Class B2 halogen-free and low-smoke materials specified in the standard GB31247, and has excellent processing performance.

[0031] 2) The present invention uses modified layer structure montmorillonite as the main carbonizing agent, mica powder and wollastonite as the porcelain skeleton, and ceramic zinc borate as the flux through extrusion processing. The product combustion test has the characteristics of no dripping, easy carbonization, no combustion support, flame retardant crusting, etc.

[0032] 3) High flame retardant and low heat release polyolefin sheath material, there are two main application occasions:

[0033] a) Produce wire and cable products that meet or exceed the flame retardant B1 level specified in the design standard GB 51348-2019 "Electrical Design Standard for Civil Buildings", and the burning dripping / particle level is not lower than D0.

[0034] b) Produce wire and cable products that meet or exceed the requirements of Article 4.0.2 of the Guangdong local standard DBJ / T 15-226-2021 "Technical Code for Fire Prevention of Wires and Cables in Civil Buildings" and meet the requirements that the non-metallic material content of wires or cables laid in the same channel is greater than 3.5L / m and less than or equal to 14L / m, the flame retardant level is not lower than the bundled flame retardant B class, and the combustion performance level is not lower than the flame retardant B1 level, the smoke toxicity is not lower than the t0 level, the corrosiveness is not lower than the a1 level, and the burning droplets / particles are not lower than the d0 level. The cable products processed with this material can be widely used in domestic high-rise public buildings, special sports buildings, special exhibition buildings, large hospitals, underground public buildings (comprehensive shopping malls, subway stations), catering and other crowded public places, etc., construction projects, rail transit, petroleum and petrochemical, and industrial and mining enterprise projects. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] In the present invention, the raw materials, reagents or equipment used can be purchased from the market.

[0037] The preparation method of the highly flame-retardant and low heat-release polyolefin sheath material provided by the present invention is mainly divided into three steps:

[0038] The first step: according to 100 parts by weight, EVA100, POE 23.5-28.6, mLLDPE 259.4-271.4, compatibilizer 17.6-26.2, silicone masterbatch 5.9-8.1, carbon black masterbatch 8.8-11.0, aluminum hydroxide 276.2-276.5 (ultrafine aluminum hydroxide, its particle size 1μm-3μm), magnesium hydroxide 111.8-138.1 (ultrafine magnesium hydroxide, its particle size 1μm-3μm), antioxidant 300#1.8-2.4, antioxidant DLTP 1.2-3.3, silane coupling agent 2.9-6.2 are mixed and stirred evenly, the stirring time is 5-9 minutes, the frequency is 8000-10000 rpm, and then mixed at a temperature of 95°C-110°C for 11-17 minutes to obtain a mixed material A.

[0039] The second step: according to 100 parts by weight, the carbonizing agent is 15.9-20.5, and the proportion is adjusted and matched according to the dripping level d0, d1, and d2 during the combustion process. The constituent materials of the carbonizing agent: quaternary ammonium salt organic intercalated nanosheet structure montmorillonite 0.9-1.6, mica powder 4.1-5.0, wollastonite 7.9-8.1, white carbon black 0.5-0.6, ceramic zinc borate 2.4-5.4 are mixed and stirred evenly, the stirring time is 3-7 minutes, the frequency is 5000-7000 rpm, and then mixed at 115°C-130°C for 5-9 minutes to obtain the carbonizing agent mixture B.

[0040] Step 3: Mix the mixtures A and B, stir for 3-7 minutes at a frequency of 5000-7000 rpm, and mix to 135°C to obtain the mixture C; extrude the mixture C through a twin-screw extruder to granulate it to obtain a highly flame-retardant and low-heat-release polyolefin sheath material, with a particle size of 3-4mm in diameter and 3mm in height in cylindrical granules or other shapes of comparable size. There is no obvious powder in the material particles. The granulation temperature is 130°C-150°C.

[0041] The proportion of ingredients of highly flame-retardant and low heat-release polyolefin sheath materials is shown in Table 1.

[0042] The proportion of carbon-forming agent components is shown in Table 2.

[0043] Table 1. Specifications of high flame retardant and low heat release polyolefin sheath material ingredients

[0044]

[0045]

[0046] Table 2. Composition of carbon forming agent

[0047]

[0048] The performance requirements of highly flame retardant and low heat release polyolefin sheath materials are shown in Table 3.

[0049] Table 3. Performance requirements of high flame retardant and low heat release polyolefin sheath materials

[0050]

[0051]

[0052] Example 1

[0053] The present embodiment discloses a preparation method of a highly flame-retardant and low-heat-release polyolefin sheath material, comprising: weighing, by weight, 100 parts of EVA, 23.5 parts of POE, 259.4 parts of mLLDPE, 26.2 parts of a compatibilizer, 5.9 parts of a silicone masterbatch, 8.8 parts of a carbon black masterbatch, 276.2 parts of aluminum hydroxide, 111.8 parts of magnesium hydroxide, 1.8 parts of an antioxidant 300#, 1.2 parts of an antioxidant DLTP, and 2.9 parts of a silane coupling agent, and obtaining a mixed material A according to a proportion and an operating method.

[0054] 15.9 parts of a carbon former were weighed out by weight, and the constituent materials of the carbon former were added: 0.9 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 4.1 parts of mica powder, 7.9 parts of wollastonite, 0.5 parts of white carbon black, and 2.4 parts of ceramic zinc borate, and mixed material B was obtained according to the proportions and operating methods.

[0055] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0056] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0057] Example 2

[0058] This embodiment discloses a method for preparing a highly flame-retardant and low heat-release polyolefin sheath material, comprising:

[0059] Weigh 100 parts of EVA, 28.6 parts of POE, 271.4 parts of mLLDPE, 26.2 parts of compatibilizer, 8.1 parts of silicone masterbatch, 11.0 parts of carbon black masterbatch, 276.5 parts of aluminum hydroxide, 138.1 parts of magnesium hydroxide, 2.4 parts of antioxidant 300#, 3.3 parts of antioxidant DLTP, and 6.2 parts of silane coupling agent by weight, and obtain mixed material A according to the ratio and operation method.

[0060] Weigh 20.5 parts of a carbon former by weight, and add the following components: 1.6 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 5.0 parts of mica powder, 8.1 parts of wollastonite, 0.6 parts of white carbon black, and 5.4 parts of ceramic zinc borate, and obtain a mixed material B according to the proportions and operating methods.

[0061] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0062] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0063] Example 3

[0064] This embodiment discloses a method for preparing a highly flame-retardant and low heat-release polyolefin sheath material, comprising:

[0065] Weigh 100 parts of EVA, 23.5 parts of POE, 259.4 parts of mLLDPE, 26.2 parts of compatibilizer, 5.9 parts of silicone masterbatch, 8.8 parts of carbon black masterbatch, 276.2 parts of aluminum hydroxide, 111.8 parts of magnesium hydroxide, 1.8 parts of antioxidant 300#, 1.2 parts of antioxidant DLTP, and 2.9 parts of silane coupling agent by weight, and obtain mixed material A according to the ratio and operation method.

[0066] Weigh 20.5 parts of a carbon former by weight, and add the following components: 1.6 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 5.0 parts of mica powder, 8.1 parts of wollastonite, 0.6 parts of white carbon black, and 5.4 parts of ceramic zinc borate, and obtain a mixed material B according to the proportions and operating methods.

[0067] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0068] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0069] Example 4

[0070] This embodiment discloses a method for preparing a highly flame-retardant and low heat-release polyolefin sheath material, comprising:

[0071] Weigh 100 parts of EVA, 28.6 parts of POE, 271.4 parts of mLLDPE, 26.2 parts of compatibilizer, 8.1 parts of silicone masterbatch, 11.0 parts of carbon black masterbatch, 276.5 parts of aluminum hydroxide, 138.1 parts of magnesium hydroxide, 2.4 parts of antioxidant 300#, 3.3 parts of antioxidant DLTP and 6.2 parts of silane coupling agent by weight, and obtain mixed material A according to the ratio and operation method.

[0072] 15.9 parts of a carbon former were weighed out by weight, and the constituent materials of the carbon former were added: 0.9 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 4.1 parts of mica powder, 7.9 parts of wollastonite, 0.5 parts of white carbon black, and 2.4 parts of ceramic zinc borate, and mixed material B was obtained according to the proportions and operating methods.

[0073] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0074] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0075] Example 5

[0076] This embodiment discloses a method for preparing a highly flame-retardant and low heat-release polyolefin sheath material, comprising:

[0077] Weigh 100 parts of EVA, 26.05 parts of POE, 265.42 parts of mLLDPE, 21.92 parts of compatibilizer, 6.99 parts of silicone masterbatch, 9.89 parts of carbon black masterbatch, 276.33 parts of aluminum hydroxide, 124.93 parts of magnesium hydroxide, 2.07 parts of antioxidant 300#, 2.25 parts of antioxidant DLTP, and 4.57 parts of silane coupling agent by weight, and obtain mixed material A according to the ratio and operation method.

[0078] 18.18 parts of a carbon former were weighed out by weight, and the constituent materials of the carbon former were added: 1.25 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 4.56 parts of mica powder, 7.96 parts of wollastonite, 0.55 parts of white carbon black, and 3.89 parts of ceramic zinc borate, and mixed material B was obtained according to the proportions and operating methods.

[0079] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0080] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0081] Example 6

[0082] This embodiment discloses a method for preparing a highly flame-retardant and low heat-release polyolefin sheath material, comprising:

[0083] Weigh 100 parts of EVA, 26.05 parts of POE, 265.42 parts of mLLDPE, 21.92 parts of compatibilizer, 6.99 parts of silicone masterbatch, 9.89 parts of carbon black masterbatch, 276.33 parts of aluminum hydroxide, 124.93 parts of magnesium hydroxide, 2.07 parts of antioxidant 300#, 2.25 parts of antioxidant DLTP, and 4.57 parts of silane coupling agent by weight, and obtain mixed material A according to the ratio and operation method.

[0084] 15.9 parts of a carbon former were weighed out by weight, and the constituent materials of the carbon former were added: 0.9 parts of quaternary ammonium salt organic intercalated nanosheet structure montmorillonite, 4.1 parts of mica powder, 7.9 parts of wollastonite, 0.5 parts of white carbon black, and 2.4 parts of ceramic zinc borate, and mixed material B was obtained according to the proportions and operating methods.

[0085] Finally, the mixed materials A and B are mixed, stirred for 3-7 minutes at a frequency of 5000-7000 rpm, and then kneaded to 135° C. to obtain a mixed material C.

[0086] The mixed material C is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat-release polyolefin sheath material.

[0087] A highly flame-retardant and low heat release polyolefin sheath material obtained according to the above embodiments 1 to 6 is tested and the measured indicators are in line with and better than the WDZ-Y-H90 performance requirements in GB / T32129-2015, especially the finished cable products are tested in the testing equipment JONSON-III cable combustion smoke density measurement system, JS / CS-IV bundled cable combustion experimental device, JS-HSMS cable combustion heat release and smoke production measurement system, and some performance indicators are shown in Table 4 below.

[0088] Table 4. Performance test

[0089]

[0090]

[0091]

[0092] It can be seen from the test results of the formula materials in the table that the material oxygen index, material heat shock resistance test, acidity of the finished product combustion released gas, finished product toxicity index, finished product smoke density, finished product combustion performance grade B1, and finished product bundled flame retardant Class A test of the high flame retardant and low heat release polyolefin sheath material prepared by the present invention in Implementation 1-6 are relatively high, and the material smoke density is particularly low. The product has excellent low smoke, halogen-free, non-toxic and comprehensive combustion and flame retardant properties, especially the carbonizing agent design scheme, which effectively ensures that the sheath material has good flame retardant crusting performance when encountering an open flame during the combustion process, and the crusted halogen-free sheath is not easy to fall off after burning to a certain extent, and when the flame retardant effect fails, the sheath is carbonized and turned into ashes. After leaving the open flame, the material automatically extinguishes, ensuring that there are no burning drips / particles within 1200s.

[0093] In summary, the high flame retardant and low heat release polyolefin sheath materials have been successfully applied to various wire and cable products with voltage levels of 26 / 35kV and below. Typical wire and cable models are: non-armored cables WDZB1-YJY, WDZB1N-YJY, WDZA-YJY-B1, WDZB-YJY-B1, WDZAN-YJY-B1, WDZBN-YJY-B1; armored cables WDZB1-YJY23, WDZB1N-YJY23, WDZA-YJY23-B1, WDZB-YJY23-B1, WDZAN-YJY23-B1, WDZBN-YJY23-B1. Products that have been applied in batches have excellent anti-cracking performance and combustion and flame retardant performance, no burning dripping, easy to form carbon, no combustion support, flame retardant crust, low smoke, and non-toxic. After testing by a third-party testing center, the actual measured performance indicators are better than the relevant national standards and the acceptance technical requirements of various construction engineering technical specifications.

[0094] The present invention is a highly flame-retardant and low-heat-release polyolefin sheath material developed based on the design acceptance standards for wire and cable products and the performance of thermoplastic 90°C halogen-free, low-smoke flame-retardant polyolefin sheath materials. The plastic particles are extruded through a twin-screw extruder with structural montmorillonite as the main carbonizing agent, mica powder and wollastonite as porcelain skeletons, and ceramic zinc borate as a flux. The performance is completely superior to the customer's technical requirements, and the finished wires and cables processed by extrusion have the characteristics of no dripping, easy carbonization, no combustion support, flame-retardant crusting, etc. in the combustion test.

[0095] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A highly flame retardant and low heat release polyolefin sheath material, characterized in that: The highly flame-retardant and low heat-release polyolefin sheath material is prepared from the following raw materials by weight: 17-21 parts of ethylene-vinyl acetate copolymer, 4-6 parts of polyolefin thermoplastic elastomer, 44.1-57 parts of metallocene linear low-density polyethylene, 3.0-5.5 parts of compatibilizer, 1.0-1.7 parts of silicone masterbatch, 1.5-2.3 parts of carbon black masterbatch, 47-58 parts of aluminum hydroxide, 19-29 parts of magnesium hydroxide, 0.5-1.2 parts of antioxidant, 0. .5-1.3 parts of silane coupling agent and 2.7-4.3 parts of carbon-forming agent; the carbon-forming agent is prepared from the following raw materials by weight: 0.15-0.34 parts of quaternary ammonium salt organic intercalation nanosheet structure montmorillonite, 0.7-1.05 parts of mica powder, 1.37-1.65 parts of wollastonite, 0.08-0.12 parts of white carbon black and 0.4-1.14 parts of ceramic zinc borate; the specific gravity of the quaternary ammonium salt organic intercalation nanosheet structure montmorillonite is 1.9g / cm 3 The antioxidant includes 0.3-0.5 parts of antioxidant 300# or antioxidant 1024 and 0.2-0.7 parts of antioxidant DLTP; the particle size of the ceramic zinc borate is 2μm-4.5μm, and the attached water is not more than 1%.

2. The highly flame-retardant and low heat-release polyolefin sheath material according to claim 1, characterized in that: The aluminum hydroxide is ultrafine aluminum hydroxide with a particle size of 1 μm-3 μm.

3. The highly flame-retardant and low heat-release polyolefin sheath material according to claim 1, characterized in that: The magnesium hydroxide is ultrafine magnesium hydroxide with a particle size of 1 μm-3 μm.

4. A method for preparing the highly flame-retardant and low heat-release polyolefin sheath material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: 1) Weighing ethylene-vinyl acetate copolymer, polyolefin thermoplastic elastomer, metallocene linear low-density polyethylene, compatibilizer, silicone masterbatch, carbon black masterbatch, aluminum hydroxide, magnesium hydroxide, antioxidant and silane coupling agent according to the formula, mixing and stirring evenly, stirring for a period of time, heating and continuing to mix, to obtain a mixed material A; 2) Weigh the raw materials of the carbonizing agent, mix and stir them evenly, stir for a period of time, increase the temperature and continue mixing to obtain a mixed material B; 3) Mixing the mixed material A obtained in step 1) and the mixed material B obtained in step 2) and stirring them, and then kneading them to obtain a mixed material C; 4) The mixed material C obtained in step 3) is extruded and granulated through a twin-screw extruder to obtain a highly flame-retardant and low heat release polyolefin sheath material.

5. The method for preparing the highly flame-retardant and low heat-release polyolefin sheath material according to claim 4, characterized in that: In step 1), the stirring parameters are: stirring frequency is 8000-10000 rpm, stirring for 5-9 minutes, heating to 95-110° C., and mixing for 11-17 minutes; In step 2), the stirring parameters are: stirring frequency is 5000-7000 rpm, stirring for 3-7 minutes, heating to 115-130° C., and mixing for 5-9 minutes; In step 3), the stirring parameters are: stirring frequency is 5000-7000 rpm, and stirring is for 3-7 minutes.

6. The method for preparing the highly flame-retardant and low heat-release polyolefin sheath material according to claim 4, characterized in that: In step 4), the granulation temperature is 130-150° C., and the highly flame-retardant and low heat-releasing polyolefin sheath material is a cylindrical granular material with a particle size of 3-4 mm in diameter and 3 mm in height, or other shapes of comparable size.

Citation Information

Patent Citations

  • Anti-flaming vitrified EVA and preparation method thereof

    CN105885197A

  • Micro-crosslinking high-flame-retardant B1-grade cable sheath material and preparation method thereof

    CN115594911A